Akibat Hukum Dikabulkannya Permohonan Pernyataan Pailit Oleh Pengadilan Niaga Medan - Sarah, Julaifa; Lubis, Elvi Zahara; Lubis, Anggreni Atmei (Universitas Medan Area, 2021)
The purpose of this research is to find out the legal consequences and the judge's consideration of granting the petition for a declaration of bankruptcy in the decision No.03/Pailit/2014/PN.Niaga.Mdn. The type of research in writing this thesis is normative which is solely used to obtain complete data as the basis for writing this scientific paper. Normative research (library study) is finding and collecting data by conducting library research on author sources using normative methods and collecting data by conducting library research on reading sources in the form of Law Number 37 of 2004 concerning UUK and PKPU, Law Number 23 of 1847 concerning the Civil Code, Law Number 8 of 1995 concerning the Capital Market, and the decision of the Medan Commercial District Court No.03/Pailit/2014 PN.Niaga-Mdn, which is a case study approach related to the issues discussed. This study concludes that in bankruptcy cases, legal consequences can be found and the panel of judges in their consideration of the parties is seen from the facts and evidence.